Modulating Endogenous Oxygen Consumption Enhanced AIEgens‐Mediated Photodynamic Therapy against Advanced Bladder Tumor. (2nd August 2021) - Hao, Jiange; Yin, Haoli; Lu, Wenfeng; Zhuang, Junlong; Chen, Mengxia; Gao, Jie; Zhu, Guanchen; Cao, Wenmin; Kan, Yansheng; Lu, Yingqiang; Guo, Hongqian
Abstract: Photodynamic therapy (PDT) plays an important role in tumor therapy. However, PDT outcomes remain poor due to the insufficient reactive oxygen species (ROS) yield of the photosensitizer and the aggravation of hypoxia in the tumor microenvironment through PDT. To solve this issue, a puissant PDT nanoparticles (NPs) platform is developed to defeat tumors by employing powerful PDT in an oxygen‐enriched tumor microenvironment and by inhibiting tumor migration through regulating hypoxia‐related pathways. Specifically, TFM, as a previously reported AIEgen, does not emit brightly but instead makes use of its nonradiative relaxation for ROS generation, along with oxygen regulator doxycycline (DOXY), both of which are encapsulated in NPs that can specifically penetrate deep into tumor tissue. After released from the NPs, TFM functions as a powerful ROS generator, and DOXY reduces endogenous oxygen consumption via regulating mitochondrial cytochrome oxidase 1, further enhancing TFM‐mediated PDT efficacy. Meanwhile, reoxygenation is observed to reduce the expression of hypoxia inducible factor‐1α and M2 macrophages induced by PDT. The amplified PDT not only strongly killed tumor but, along with the downregulated hypoxia related pathways during the post‐PDT process, inhibited tumor migration. In summary, such NPs exhibit potent anti‐tumor effects for advanced bladder cancer therapy. Abstract : Puissant photodynamic therapy (PDT) nanoparticles platform to defeat tumor by employing powerful reactive oxygen species generator in an oxygen‐enriched tumor microenvironment is reported. The amplified PDT not only strongly kills tumors but, along with the downregulated hypoxia‐related pathways during the post‐PDT process, inhibits tumor migration, exhibiting potent anti‐tumor effects for advanced bladder cancer therapy.